Condition optimization for exfoliation of two dimensional titanium carbide (Ti3C2Tx). (30th January 2018) - Rajavel, Krishnamoorthy; Ke, Tao; Yang, Kun; Lin, Daohui
Abstract: The new class of 2D MXene material exfoliated from transition metal carbides receives increasing research interest due to its extraordinary properties and high potential in energy and environmental applications. However, the exfoliation of Ti3 C2 T x, a widely studied MXene, from its precursor Ti3 AlC2 by chemical etching in HF solution remains to be optimized. This study investigated the optimum exfoliation condition through systematic evaluating potential effects of reaction parameters, including the weight ratio of Ti3 AlC2 in HF solution, etching time, reaction temperature, repeating etching, and sonication, on the yield, purity, and structure of produced Ti3 C2 T x . Results show that a high weight percentage (5 wt%) of Ti3 AlC2 etching at 50 °C for 36 h produced highly exfoliated MXene material. Etching at lower weight percentages (0.6–2.5 wt%) of Ti3 AlC2 resulted in observable byproduct (AlF3 ). Degradation of MXene layers with AlF3 enrichment was observed under prolonged etching or higher temperatures. Room temperature etching failed to exfoliate Ti3 AlC2 and the repeated etching denatured the MXene material. Introduction of controlled sonication during the etching produced highly exfoliated MXene with minimum etching time, which can be a promising alternative for high quality MXene production.